Aggressive Angiomyxoma: A Rare Tumor of Male Pelvic Cavity - Celik, Suleyman Utku (2018)
Aggressive angiomyxoma is an uncommon, benign, slow-growing, and locally infiltrative soft tissue neoplasm which is located primarily in the genital region and pelviperineal interstitial tissue of female patient in the fourth decade of life. Its occurrence in male patients is even more unusual and commonly appears at a later age. The mainstay of treatment typically involves surgical excision with tumor-free margins, and despite complete resection, local recurrences are common. Here, an unusual case of aggressive angiomyxoma occurring in the pelvic region of a 55-year-old man and its treatment is discussed due to its rarity.